Revision of the Stegana nigrolimbata species group (Diptera: Drosophilidae) from the Oriental Region - Cao, Hua-Zhi; Chen, Hong-Wei (Zootaxa, 2008)
The Stegana nigrolimbata species group from the Oriental Region is revised, and composed of seven species, five newly described, S. (S.) belokobylskiji Sidorenko from Vietnam, S. (S.) nigrolimbata Duda, S. (S.) brevibarba sp. nov. and S. (S.) xiaoleiae sp. nov. from south China, S. (S.) capillaria sp. nov., S. (S.) longibarba sp. nov. and S. (S.) multiclavata sp. nov. from east Malaysia. A key to the all species of the group is provided.